Application of Sharing Risk in Musharakah Contracts - Abdi, Muhammad Nur; Hamzah, Nasir (Universitas Muhammadiyah Sorong, 2024)
This study provides new empirical evidence regarding the application of sharing risk in Islamic banking in Indonesia. The focus of this research is to analyze the application of sharing risk in musyarakah financing, formulating sharing risk in musyarakah financing. The research method used is descriptive research which is analyzed qualitatively. Data sources were obtained from employees of Bank Syariah Indonesia account maintenance unit, Risk unit and collection unit, as well as documentation. Data analysis was done by data reduction, data presentation and conclusion drawing. The results showed that: 1) the implementation of risk sharing in musharakah financing at Bank Syariah Indonesia has not been fully fulfilled; 2) The risk sharing formulation can be implemented by proposing several improvements including the existence of a communication room where every customer's business development will be reported per period with the concept of joint business, then if a risk occurs it should be included in the communication room so that it can be discussed with both parties to formulate the best steps; Our evidence suggests that regulators further strengthen the Islamic banking system through musharakah contract reform and focus on the risk sharing system, especially the contracting parties.